(im)Material Geographies: From Poetics of Terraforming to Earth Scripts - Tymon Adamczewski (Anglica. An International Journal of English Studies)
The article explores the work of two contemporary poets, Alice Oswald and J.R. Carpenter, with reference to the material and immaterial aspects of their poetic projects. It is argued that although disparate in their form, both artists’ works are linked by their interest in the environmental forces as (im)material manifestations of more-than-human agency. In this sense they can be seen as belonging to a longer and broader strain of poetic endeavours (like concrete poetry and land art) that struggle to problematise the relationship between form and meaning. The article also employs the notion of earth scripts which allows to see such poetic and artistic practices as forms of descriptions of the earth characterized by differing degrees of sensitivity to the environmental challenges posed by the Anthropocene.